The Relationship Between Emotional Memory (Memories) and Protective Mechanisms of Young People - Nevoienna, Olena; Yarosh, Nina (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The article examines the phenomenon of emotional memory of a person, which is understood as the memory of emotional states that took place in the past. A significant link has been established between emotional memory and protective mechanisms in young people, with protective mechanisms processing memories of both the distant and recent past in inverse proportion. It is noted that the "pleasant" in content, strongly emotionally colored events of the distant past in young people are reproduced proportionately in the opposite direction with such protective mechanisms as "regression", "denial", "projection", the work of these protective mechanisms, but in different ways. aimed at eliminating events that could in any way disrupt or damage the work of the psyche. It has been determined that young people's memories, which are classified as "new" in terms of content, both old and recent, are related to the protective mechanisms of "displacement" and "rationalization". The authors point out that "displacement" combines "new" information immediately with existing or displaces it if it poses a threat to the individual's psyche.